2022
DOI: 10.3390/insects13030255
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Plectranthus amboinicus Essential Oil against the Stable Fly Stomoxys calcitrans (Diptera: Muscidae) and the Horse Fly Tabanus megalops (Diptera: Tabanidae)

Abstract: The stable fly, Stomoxys calcitrans (Diptera: Muscidae), and the horse fly, Tabanus megalops (Diptera: Tabanidae), are important ectoparasites of livestock in Thailand. These species affect animal health and cause economic losses. This study investigated the insecticidal activity of Plectranthus amboinicus essential oil against S. calcitrans and T. megalops through contact and fumigant toxicity tests and evaluated the effects of the essential oil on these flies through histopathological and scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…It also inhibits the biofilm formation of other pathogenic microorganisms, such as Streptococcus mutans, Streptococcus pyogenes, and S. aureus [ 50 , 51 , 52 ]. C. amboinicus is rich in monoterpenes, including carvacrol, thymol, eugenol, chavicol, and ethyl salicylate [ 37 , 49 , 53 ]. The 18 compounds identified in CEO in this study represent 99.84% of the total essential oil and include carvacrol (56.65%), p-cymene (10.89%), and γ-terpinene (9.33%); these three compounds alone comprise 76.87 % of the total essential oil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It also inhibits the biofilm formation of other pathogenic microorganisms, such as Streptococcus mutans, Streptococcus pyogenes, and S. aureus [ 50 , 51 , 52 ]. C. amboinicus is rich in monoterpenes, including carvacrol, thymol, eugenol, chavicol, and ethyl salicylate [ 37 , 49 , 53 ]. The 18 compounds identified in CEO in this study represent 99.84% of the total essential oil and include carvacrol (56.65%), p-cymene (10.89%), and γ-terpinene (9.33%); these three compounds alone comprise 76.87 % of the total essential oil.…”
Section: Discussionmentioning
confidence: 99%
“…This result differs from that reported by da Costa et al, who found thymol to be the major constituent (64.3%), followed by p-cymene (10.3%), γ-terpinene (9.9%), and β-caryophyllene (2.8%) [ 54 ]. Previous studies have reported that the phytochemical composition of CEO is significantly influenced by the cultivation location, processes, and methods of essential oil extraction [ 25 , 37 ]; for example, steam distillation produced higher levels of carvacrol in C. amboinicus essential oil than those produced via the hydrodistillation method [ 37 ]. CEO at MIC had excellent effects against all clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They consist of various secondary metabolites such as tannins, phenolic compounds, alkaloids, and flavonoids, which assist in enhancing growth and immunity responses 20 . P. amboinicus and O. sanctum comprise some main phytochemical constituents such as α-Cubebene, α-Copaene, alpha-Humulene, Beta-caryophyllene, Carvacrol, Eugenol, Para-cymene, Limonene, Apigenin, Rosmarinic acid, Ursolic acid, Oleanolic acid, Luteolin, Beta-sitosterol, etc., 17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . As per the literature study, these are typically the components of major interest with bioactive properties that are well established.…”
mentioning
confidence: 99%